Reef-Building Corals Do Not Develop Adaptive Mechanisms to Better Cope With Microplastics - Rades, Marvin; Schubert, Patrick; Wilke, Thomas; Reichert, Jessica (Frontiers in Marine Science, 2022)
Microplastics are omnipresent in the oceans and threaten marine animals through physical contact or ingestion. Short-term studies have already shown that reef-building stony corals respond differently to microplastics than natural food. However, it remains unknown whether corals exhibit acclimation mechanisms to combat the effects of microplastic exposure. Specifically, the long-term effects of microplastics on the feeding and defense behavior of reef-building corals remain unexplored. Therefore, the goal of this study was to infer potential acclimation mechanisms in the behavior of the corals. For this, four reef-building species (Acropora muricata, Porites lutea, Pocillopora verrucosa, and Heliopora coerulea) were exposed in a long-term experiment to microplastics for 15 months. Subsequently, coral feeding rates on microplastics and natural food (Artemia sp. cysts), feeding discrimination, and reactions to both were assessed in a 24 h pulse exposure experiment. The results showed that corals’ feeding rates did not decrease after long-term exposure to microplastics. Similarly, the feeding discrimination (i.e., ratio of feeding on microplastics and natural food) did not differ after long-term exposure to microplastics. Moreover, corals showed no changes in defense behavior (i.e., mucus production or extrusion of mesenterial filaments) against microplastics. These findings suggest that symbiotic, reef-building corals do not develop mechanisms to adapt to long-term microplastic exposure. Thus, microplastic pollution might constitute a constant stressor for coral organisms, likely leading to sustained energy expenditures and impaired health.